Prevalence and management of anemia and impact of treatment burden on health-related quality of life in chronic kidney disease and dialysis patients - Amjad Khan; Sadia Ghulam Hussain; Saima Mushtaq; Sameen Abbas; Yalin Dong; Weiyi Feng; Yu Fang (Journal of Pharmaceutical Policy and Practice)
Background Anemia management in chronic kidney disease (CKD) is a significant challenge for healthcare professionals worldwide. The extensive management of CKD and its complications is directly linked with a substantial treatment burden, which impacts quality of life (QoL). This study aimed to assess the prevalence and management of anemia and to evaluate the treatment burden and its impact on the QoL of CKD and dialysis patients in Pakistan.Methodology A multicenter prospective observational study was conducted in three hospitals. A total of 170 patients were enrolled, with 156 available for follow-up after six months. Their prior consent was obtained. Each participant was interviewed in person and received a data collection form.Results At baseline, the prevalence of anemia among CKD (stage 3–5) and dialysis patients was 78.7% and 94.7%, respectively. Patients on dialysis used more erythropoietin stimulating agents (ESAs), with 38.6% at baseline and 40.8% by month six, compared to non-dialysis CKD patients. Oral iron was used by 6.2% of stage 3, 25% of stage 4, 20% of stage 5 patients, and 6.6% of dialysis patients at baseline. At the six-month follow-up, 42.8% of CKD and 33.8% of dialysis patients achieved the target hemoglobin level. Dialysis patients had a higher treatment burden compared to CKD at baseline (77.4±10.6 vs 59.3±13.3) and at six-month visit (79.3±11.1 vs 59.1±14.5). The multiple regression analysis showed that treatment burden had a significant association with age, disease duration, and comorbidity at baseline. There was a significant negative correlation between overall treatment burden and QoL, indicating that QoL decreases as treatment burden increases.Conclusion Anemia was prevalent, and its management was suboptimal in this study. The overall treatment burden score was high in dialysis patients, negatively affecting the QoL.